PENGARUH KEPERCAYAAN DAN KOMITMEN TERHADAP KUALITAS HUBUNGAN DAMPAKNYA PADA KINERJA RANTAI PASOKAN (Studi Kasus Produksi dan Distribusi Dedak pada PD Sederhana) - Mukhsin, Moh. (Jurnal Manajemen, 2017)
The purposes of this study is to determine whether there is influence of Trust and Commitment to Supply Chain Performance with Quality of Relation as an intervening variable,Ã‚Â  Production and Distribution case study of Dedak on PD. Sederhana. Variables used in this research are trust and commitment as independent variables, Supply Chain Performance as Dependent variable, and quality of relation as intervening variable. This research used quantitative method by using descriptive research and causal research. Data from the 4 variables were analyzed by using Structural Equation Model (SEM) in Software SmartPLS (Partial Least Square) version 1.0. The number of samples used in this study were 57 respondents.Based on the result of data analysis, it can be concluded that there is positive and significant relation among trust and commitment to the quality of relation, whereas there is positif significant relation among Trust and commitment to supply chain performance. The result of analysis indicate that the quality of relation is able to mediate trust and commitment influence to supply chain performance.